Caring about health: improving the health of looked after and accommodated children in Scotland. An A-Z health resource pack for staff and carers - Irene Stevens (Scottish Journal of Residential Child Care)
This national resource pack has been published by NHS Health Scotland. The main aim of the pack is to support those caring for looked after and accommodated children in residential and foster care settings throughout Scotland. Presented in A-Z format (in 10 segments), the pack provides easy access to health information, sources of help and advice, and relevant websites. It also advocates a wider, more holistic approach to health.